Pengaruh PDRB, kemiskinan, pengangguran, dan PMA terhadap ketimpangan pendapatan di Daerah Istimewa Yogyakarta - Yana Fitria; Ruth Eviana Hutabarat (Jurnal STEI Ekonomi, 2026)
This study aims to examine the effects of Gross Regional Domestic Product at Constant Prices (GRDP), the number of poor people, the open unemployment rate, and foreign direct investment (FDI) on income inequality across regencies and municipalities in the Special Region of Yogyakarta. The study employs a quantitative approach using panel data covering five regencies/municipalities during the 2015–2024 period. Data were analyzed using panel data regression with the assistance of EViews 12 software. The findings reveal that the open unemployment rate has a positive and significant effect on income inequality, whereas foreign direct investment has a negative and significant effect. In contrast, GRDP and the number of poor people have no significant effect on income inequality. These findings indicate that income inequality in the Special Region of Yogyakarta is more strongly influenced by labor market conditions and the distribution of investment than by economic growth and aggregate poverty levels. The results of this study are expected to provide insights for local governments to formulate more inclusive development policies by expanding employment opportunities and more equitably distributing investment to reduce regional income inequality.